Implementation Of Progressive Muscle Relaxation Therapy To Lower Blood Pressure In Hypertension Patients At The Muara Bangkahulu Community Health Center, Bengkulu City In 2025 - Sari, Winda Permata; Hidayat, YanceHidayat; Aprianti, Delta (Utami Publisher, 2025)
Hypertension is a non-communicable disease often called a silent killer because it can cause serious complications and even sudden death. According to WHO data from 2022, there are 1.28 billion adults with hypertension, and this number is predicted to increase to 1.5 billion by 2025. This study aims to determine the implementation of progressive muscle relaxation therapy to reduce blood pressure in hypertensive patients. The method used is a descriptive case study on a 47-year-old female patient with stage 1 hypertension. The intervention was given for six consecutive days, with a duration of 15 minutes per session. The results showed a decrease in average systolic blood pressure of 7.1 mmHg and diastolic blood pressure of 3.6 mmHg, as well as a decrease in headache complaints from a scale of 4 to 2. Conclusion: progressive muscle relaxation therapy is effective in helping to reduce blood pressure in hypertensive patients, so it can be an alternative non-pharmacological intervention in health services.